Elucidating the Role of Pelargonidin-3-O-Glucoside on C1QL3, CYBB, and CYTIP Involved in Glucose Metabolism: An In Silico Approach - Krishna Aravind (Wolters Kluwer Medknow Publications, 2024)
AimThe metabolism of glucose is carefully regulated by several chemical elements and plays a critical part in preserving cellular energy balance. Our study investigates possible connections between the essential proteins CYTIP, C1QL3, and CYBB, which are involved in the metabolism of glucose, and pelargonidin, a naturally occurring plant chemical. The underlying mechanisms of pelargonidin's anti-diabetic effects are still unknown. Materials and MethodsWe examine the binding affinities and possible binding sites between pelargonidin and C1QL3/CYBB AND CYTIP using molecular docking simulations. The results demonstrate favorable docking scores and potential binding sites, suggesting the formation of stable complexes between pelargonidin and the target proteins. ResultsThis finding means that pelargonidin may modulate the function of C1QL3 and CYBB, CYTIP consequently influencing glucose metabolism. ConclusionThis study provides a foundation for future experimental investigations to validate the predicted interactions and explore the mechanisms through which pelargonidin affects glucose metabolism. Understanding these molecular interactions could lead to the development of new therapeutic strategies for glucose metabolism and its related disorders.